How Media Coverage of Focusing Events Impacts Agenda Setting: Case Studies of Beslan School Siege (Russia) and Peshawar School Attack (Pakistan) - Masood Ahmed; Muhammad Atif Khan; Adeel Arshad; Majida Yousaf (ACADEMIA International Journal for Social Sciences, 2025)
This paper analyzes the Beslan School Siege in Russian in 2004 and Peshawar School Attack in Pakistan in 2014 on the criteria of focusing events given by Thomas Birkland and proves that these events were focusing events. The paper analyses different theories regarding focusing events and agenda-setting in the literature review section. A detailed discussion of both the events and resulting policies follows. A structured focus comparison of both the events is made according to the criteria of focusing events given by Thomas Birkland. The media attention given to both the events is analyzed, and it is shown that how powerful policy actors in Russia and Pakistan used the media attention to further their own policies and solutions to tackle the problem of terrorism faced by both nations.